Hamilton's Object – a clumpy galaxy straddling the gravitational caustic of a galaxy cluster: constraints on dark matter clumping. Issue 2 (17th May 2021) - Griffiths, Richard E; Rudisel, Mitchell; Wagner, Jenny; Hamilton, Timothy; Huang, Po-Chieh; Villforth, Carolin
ABSTRACT: We report the discovery of a 'folded' gravitationally lensed image, 'Hamilton's Object', found in a HST image of the field near the active galactic nucleus SDSS J223010.47-081017.8 (which has redshift 0.62). The lensed images are sourced by a galaxy at a spectroscopic redshift of 0.8200 ± 0.0005 and form a fold configuration on a caustic caused by a foreground galaxy cluster at a photometric redshift of 0.526 ± 0.018 seen in the corresponding Pan-STARRS PS1 image and marginally detected as a faint ROSAT All-Sky Survey X-ray source. The lensed images exhibit properties similar to those of other 'folds' where the source galaxy falls very close to or straddles the caustic of a galaxy cluster. The folded images are stretched in a direction roughly orthogonal to the critical curve, but the configuration is that of a tangential cusp. Guided by morphological features, published simulations and similar 'fold' observations in the literature, we identify a third or 'counter'-image, confirmed by spectroscopy. Because the fold-configuration shows highly distinctive surface brightness features, follow-up observations of microlensing or detailed investigations of the individual surface brightness features at higher resolution can further shed light on kpc-scale dark matter properties. We determine the local lens properties at the positions of the multiple images according to the observation-based lens reconstruction of Wagner. The analysis is in accordance with a mass density which hardly varies on an arcsecond scale (6 kpc) over the areas covered by the multiple images.